2013
DOI: 10.1007/s00383-013-3324-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic pyloric stenosis in premature infants: evaluation of sonographic criteria and short-term outcomes

Abstract: Premature infants with HPS have a higher female preponderance than expected. Ultrasound measurements in premature infants with HPS are not affected by weight, corrected gestational age or duration of symptoms. In addition, they have a longer hospital stay and increased complication rate compared to term infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
2
15
0
1
Order By: Relevance
“…In our study, mean PR was close to these values in infants with IHPS. Also, both age and weight were not significantly correlated with PR, which was similar to the results of the above mentioned studies [7,8].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In our study, mean PR was close to these values in infants with IHPS. Also, both age and weight were not significantly correlated with PR, which was similar to the results of the above mentioned studies [7,8].…”
Section: Discussionsupporting
confidence: 89%
“…Iqbal et al [14] reported that age had a positive correlation with PMT which is consistent with our results; however, unlike us they found that weight had a positive correlation with PMT and age positively correlated with PL. In their study including premature infants, Cascio et al [8] found that PMT and PL were not affected by weight and corrected gestational age. Forster et al [11] also found no significant correlation between age, weight or prematurity and sonographical diagnosis of IHPS, regarding PMT and PL.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations